2017
DOI: 10.1038/s41467-017-01855-z
|View full text |Cite
|
Sign up to set email alerts
|

Gαi is required for carvedilol-induced β1 adrenergic receptor β-arrestin biased signaling

Abstract: The β1 adrenergic receptor (β1AR) is recognized as a classical Gαs-coupled receptor. Agonist binding not only initiates G protein-mediated signaling but also signaling through the multifunctional adapter protein β-arrestin. Some βAR ligands, such as carvedilol, stimulate βAR signaling preferentially through β-arrestin, a concept known as β-arrestin-biased agonism. Here, we identify a signaling mechanism, unlike that previously known for any Gαs-coupled receptor, whereby carvedilol induces the transition of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 50 publications
4
74
0
1
Order By: Relevance
“…In apparent contrast, other studies have demonstrated an essential role for β-arrestin in some pathways regulating ERK activation 16 . Interestingly, two decades of work has demonstrated that for G αi coupled receptors, β-arrestin-mediated ERK activation is invariably pertussis toxin sensitive 22,23,24 . However, how the G αi and β-arrestin transducers cooperate in this pathway has remained obscure.…”
Section: Introductionmentioning
confidence: 99%
“…In apparent contrast, other studies have demonstrated an essential role for β-arrestin in some pathways regulating ERK activation 16 . Interestingly, two decades of work has demonstrated that for G αi coupled receptors, β-arrestin-mediated ERK activation is invariably pertussis toxin sensitive 22,23,24 . However, how the G αi and β-arrestin transducers cooperate in this pathway has remained obscure.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, carvedilol can promote β-arrestin signaling while acting as an inverse agonist towards G protein signaling (Wang et al, 2017). This type of β-arrestin signaling has been shown to have anti-apoptotic effects (Ahn et al, 2009;DeFea et al, 2000;Povsic et al, 2003) that may prevent Q344X rod death.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous application of biased ligands to replace the missing peptides attenuates the development of the disease (Yang et al 2017b). Conversely, the β-agonist carvedilol has been proposed as a β-arrestin biased ligand, beneficially and selectively activating this pathway compared to a balanced compound (Wang et al 2017), although it should be noted there may also be a significant contribution from α1-adrenoreceptor antagonism. While both ET receptors are internalized by β-arrestin and dynamin/clathrin-dependent mechanisms, ET A are recycled to the plasma membrane for further signaling while ET B are targeted to lysosomes and degraded (Bremnes et al 2000).…”
Section: Biased Signaling In the Et Pathwaymentioning
confidence: 99%